Waldemar Zubrzycki, Aleksander Babiński, Procedury bezpieczeństwa w Unii Europejskiej (Safety Procedures within the European Union), Difin, Warsaw 2017, 200 pages. - Willa, Rafał (The Copernicus Journal of Political Studies, 2018)
review